PENGARUH FAKTOR LINGKUNGAN FISIK RUMAH TERHADAP KEJADIAN KUSTA ANAK DI KABUPATEN PASURUAN - Nisa Amira; Lilis Sulistyorini (Poltekkes Kemenkes Surabaya, 2016)
Pasuruan Regency is one of leprosy endemic area in East Java Region. The number of new cases of leprosytends to decrease every year. Among the new cases of leprosy in Pasuruan Regency, there are childhood leprosycases. Childhood leprosy is every leprosy cases that affected children between the age of 0-14. The existence ofnew leprosy cases in children indicates that there’s still active leprosy infection in certain places. The objective ofthis study is to analyze the effect of Physical Environment of Housing toward Childhood Leprosy in PasuruanRegency. This study is an analytical observational study using case-control design. The number of each case andcontrol sample are 16, so the number of all samples are 32. The independent variables of this study are the areaof children’s bedroom ventilation, walls material, floors material, children’s bedroom light exposure, children’sbedroom density, and children’s bedroom humidity. The dependent variable of this study is the incidence ofchildhood leprosy in Pasuruan Regency between the age of 0-14. All data are acquired by observing andmeasuring the respondent’s houses. The analysis of the influence of independent variables to dependent variableis using binomial logistic regression. The result of logistic regression shows that childhood leprosy in PasuruanRegency are determined by the area of children’s bedroom ventilation Keywords:childhood leprosy, physical environment of housing, density, ventilation